Mapping contemporary Catholic politics in Italy. Issue 3 (26th May 2016) - Bailey, Tom; Driessen, Michael
Abstract: This editors' introduction opens a special issue of the Journal of Modern Italian Studies on the topic of 'Mapping Contemporary Catholic Politics in Italy'. It briefly identifies the political, sociological and ideational changes that have occurred in Catholic politics since the collapse of the Democrazia Cristiana party, and introduces the contributions to the special issue, highlighting the common threads and the important divergences in their analyses.